Synthesis of Mono-and Diacylglycerol Using High Shear Reactor - Rohana, Nanda Legiasa Rabiul Tsani; Millati, Ria; Yanti, Rini; Ardani, Aulia Safrina; Hidayat, Chusnul (Department of Science and Technology, 2023)
This study aimed to obtain the best characteristics of a product containing a mixture of high mono-and diacylglycerol (MDAG) from a palm olein and coconut oil blend through glycerolysis-interesterification using a high shear reactor. The most optimum reaction was performed at a relatively low temperature (120 °C), 3 NaOH as a catalyst, a 12 molecular sieve, and an agitating speed of 2000 rpm. The evaluated factors were palm olein: coconut oil ratios (70:30, 60:40, 50:50, 40:60, and 30:70) and oil: glycerol ratios (1:3, 1:4, 1:5, 1:6, and 1:7). The results showed that palm olein: coconut oil ratio had a significant effect on melting point (MP), slip melting point (SMP), hardness, and emulsion capacity and stability, but it did not have a significant effect on MDAG concentration (P > 0.05). Besides, modifying a high-shear reactor with a vacuum pump and molecular sieve caused a decrease in water content in the system, subsequently reducing free fatty acid (FFA) significantly (P < 0.05). The reaction condition at palm olein: coconut oil ratio of 50:50 and oil: glycerol ratio of 1:5 produced the highest MDAG concentration (58.28) with FFA, water content, hardness, SMP, MP, emulsion capacity, and emulsion stability about 6.75, 7.00, 3.93 N, 33.23 °C, 35.57 °C, 62.66, and 61.59, respectively. Thus, glycerolysis-interesterification of palm olein and coconut oil blend in a high shear reactor is a promising alternative to produce a product containing high MDAG with better characteristics at a relatively low temperature. The product can be used for chocolate spread based on its emulsion capacity, stability, and semi-solid hardness.